Process and Performance: Matters of Quality in Community-Based Theatre - Butterwick, Shauna; Selman, Jan (Art/Research International, 2025)
In this dialogic exploration of our shared experience of a community-based theatre project (CBT), we consider decisions, processes, and activities we selected to enhance the power of this arts-based research (ABR) form. We chose CBT as we believed it was the best approach to explore activists’ experiences of the challenges of feminist coalition politics within and across equality-seeking organisations. Our dialogues surfaced some key aspects of community theatre-making which we believe contribute to its quality, that is, its value and power to lead us to collaborate, listen deeply, tell stories, imagine a different world, and rehearse for action.